A reactive transport approach to modeling cave seepage water chemistry I: Carbon isotope transformations. (15th October 2021) - Druhan, Jennifer L.; Lawrence, Corey R.; Covey, Aaron K.; Giannetta, Max G.; Oster, Jessica L.
Highlights: Multi-year soil and cave monitoring of cations, stable carbon and radiocarbon signatures. Calibration of an isotope-enabled reactive transport model. Model demonstrates balance between dissolution of radiocarbon-dead limestone and gas phase exchange between the epikarst and overlying atmosphere. Stable carbon isotopes are strongly influenced by temperature-dependent fractionation among coexisting inorganic carbon species. Abstract: The majority of Critical Zone research has emphasized silicate lithologies, which are typified by relatively slow rates of reactivity and incongruent weathering. However, the relatively simpler weathering of carbonate-dominated lithology can result in secondary mineral deposits, such as speleothems, which provide a long-term archive for Critical Zone processes. In particular, carbon isotopic variability in speleothems has the potential to provide records of changes in vegetation, soil respiration, carbon stabilization in deep soils, and/or chemical weathering in the host rock. Despite this opportunity to reconstruct many Critical Zone processes, multiple influences can also make interpretion of these speleothem carbon isotope records challenging. The integration of observational data and simulations specific to karst systems offers an interpretive framework for these unique time-averaged records accumulated through the evolution of carbonate landscapes. Here, we present a forward and process-based reactive transport simulation based on a multi-year monitoring study of Blue Spring Cave in central Tennessee, USA. The simulations describe the fluid-driven weathering of limestone including explicit tracking of dissolved calcium, stable carbon, and radiocarbon isotope ratios based on reaction rates calibrated through laboratory batch reaction data. We find that calcium concentrations and radiocarbon isotope ratios are strongly influenced by the combination of fluid flow rate and soil CO2 content, and require rapid gas phase communication between the overlying soil boundary condition and interior karst to sustain both elevated limestone weathering rates and relatively modern radiocarbon signatures. Stable carbon isotopes are largely dictated by temperature-dependent equilibrium fractionation among contemporaneous species. These simulations are extended to a wide range of parameter space to demonstrate the environmental factors that these isotope proxies record.